(untitled) (Global Business Management Review (GBMR), 2022)
In the current business competition, firms face strong challenges and further threats to the sustainability of its business. So, to remain in the turbulent markets and operate with the very short life cycle of products as well as the rapid changes of customers’ needs and wants, firms need to possess crucial resources to establish and keep the competitive advantage for a long time among current and potential competitors. However, previous studies indicate that IT human resources play a significant role in sustaining competitive advantage of the firms especially in the dynamic environment and almost studies done within large firms and in developed countries. In addition, studies in the small and medium enterprise still very few if any especially in developing countries. Therefore, the aim of this paper is to fill the gap that discovered from previous studies where IT human resources, core competence and sustaining competitive advantage has been ignored. Hence, this study seeks to establish a theoretical framework and explore the relationship between IT human resources and core competence on the firm sustaining competitive advantage under resource-based view theory from developing country such as Malaysia.